The Power of Branding on Reviving Ride-Hailing’s Customer Recovery after Service Failure - Wahyu Joko Priyono; Aminah Swarnawati (Journal of Consumer Sciences, 2024)
Ride-hailing services are important part of urban transportation in Indonesia in Indonesia. While they provide convenience and flexibility to millions of customers, service failures are inevitable and can significantly impact customer satisfaction and retention. Therefore, effective recovery strategies are essential. This study examined the impact of brand image and passion on affective commitment and brand equity, which in turn affect service recovery satisfaction and repatronage intentions in Jakarta. It focuses on the emotional and psychological mechanisms that drive service recovery satisfaction and repatronage intentions, in contrast to previous studies that primarily focused on general consumer behavior. Using a quantitative survey research design, data was collected through face-to-face interviews using a structured questionnaire administered to 103 respondents selected via convenience sampling. The Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique was employed due to its capacity to effectively manage complex models with smaller samples. It is suitable for the exploratory nature of this study. The findings indicate that brand image positively affects affective commitment and brand equity. Brand passion strongly influences both affective commitment and brand equity. Affective commitment significantly impacts recovery satisfaction and repatronage intentions, while brand equity also predicts both outcomes. These results highlight the importance of strategic branding and affective commitment in the service recovery process and provide important insights for improving customer retention strategies in the competitive ride-hailing sector. Despite the findings, this study has several limitations. Its focus on Gojek customers in Indonesia, the cross-sectional design, and omission of moderating factors may limit the generalizability and depth of the findings. These suggest the need for more diverse samples, longitudinal studies, and the inclusion of additional constructs in future research. The study not only contributes to the theoretical framework of consumer-brand relationships but also provides practical implications for brand managers aiming to enhance customer repatronage intention through effective recovery efforts.